Mainstreaming support for the ICC in the EU's policies - Bekou, Olympia; Mistry, Hemi (EU Publications Office, 2014)
The European Union and its Member States have been the staunchest supporters of the ICC system of international criminal justice in the last two decades. That system is now at a critical juncture. With a view to the future, it is necessary to examine how the ICC can overcome the current challenges and build upon its successes to date. And more specifically, how the EU and its Member States can, and should, help the ICC in this respect. By critically assessing the EU’s performance to date in mainstreaming support for the ICC throughout its policies and activities, this study addresses these questions